Marker assisted pyramiding of stem rust, leaf rust and powdery mildew resistance genes for durable resistance in wheat (Triticum aestivum L.) - Kumaran, Vikas Venu; Murugasamy, Sivasamy; Paramasivan, Jayaprakash; Prasad, Pramod; Kumar, Subodh; Bhardwaj, Subhash Chander; Murugan, Geetha; Rebekah, Nisha; Paneer, Shajitha; Peter, John (Journal of Cereal Research, 2021)
Wheat production is essential for food security. Stem and leaf rust diseases continually pose threat to wheat production. In recent years, climate change and intensive crop cultivation practices are making powdery mildew as a potential threat to wheat production. Deploying resistant cultivars are the most economic, reliable and sustainable way to manage the stem rust, leaf rust and powdery mildew of wheat. Using conventional selection system, it is difficult to select two or more genes in a single genotype. In such a situation, phenotype neutral selection based on marker-trait association along with seedling and adult plant reaction become inevitable. Stem rust, leaf rust and powdery mildew resistance genes, Sr24/Lr24, Sr26 and Sr36/Pm6 were pyramided in the background of nine Indian wheat cultivars through marker assisted backcross approach. The presence of the rust and powdery mildew resistance genes were confirmed using microsatellite markers such as Sr24#12 (Sr24/Lr24), Sr26#43 (Sr26) and stm773 (Sr36/Pm6) in the pyramided lines. Stable lines were selected at BC3F4 generation. Seedling and adult plant reaction of pyramided lines showed resistance to most of the stem and leaf rust pathotypes prevailing in India. Using gene pyramids (Sr24/Lr24, Sr26 and Sr36/Pm6) that confer resistance to the predominant pathotypes of stem rust, leaf rust and powdery mildew could impart durability to the cultivars than single gene deployment.